Saving the World at Business School. Part 2 : A Conversation with Andy Hoffman. - Burton, Howard (Toronto : Open Agenda Publishing, 2021)
This book is based on an in-dept, remotely filmed conversation in December 2020 between Howard Burton and Andy Hoffman, Holcim Professor of Sustainable Enterprise at the University of Michigan's Ross School of Business and School of Environment and Sustainability. They discuss Andy Hoffman's research and scholarly insights which are extremely relevant to today's society. Andy Hoffman is passionately committed to encouraging fellow academics to play a much stronger role in communicating knowledge, facts and information to the regular public and politicians which has culminated into his two new.
Intro -- A Note on the Text -- Introduction -- The Conversation -- I. Reprise -- II. Truth Decay -- III. The Value of Wisdom -- IV. Investigating Rewards -- V. Concrete Opportunities -- VI. Management as a Calling -- VII. Opinionated Ignorance -- VIII. Qualified Optimism -- IX. Spreading the Word -- X. Getting Personal -- XI. Shattered Leadership? -- Continuing the Conversation
Description based upon print version of record.
JSTOR
Keywords: Hoffman, Andrew J., -- 1961- -- Interviews; Education, Higher -- Political aspects; Research -- Political aspects; Learning and scholarship -- Political aspects; College teachers -- Political activity; Communication in learning and scholarship; Enseignement supérieur -- Aspect politique; Recherche -- Aspect politique; Savoir et érudition -- Aspect politique; Communication savante; Business Communication; BUSINESS & ECONOMICS; Development; College teachers -- Political activity; Communication in learning and scholarship; Education, Higher -- Political aspects; Learning and scholarship -- Political aspects; Research -- Political aspects; Interviews